A brief history of evolutionary biology - Blackstone, Neil (Henry Stewart Talks, 2016)
Uniformitarianism, Lamarckism and Darwin's theory, Mendel’s work and the science of genetics, The modern synthesis: a mechanistic basis for variation and heredity, Molecular biology: the age of biological information, Rethinking gradual progressive evolution, Evolutionary biology in the age of genomics, Eugenics, the dark chapter of evolutionary biology, Group-level selection and evolution of morality